Updating history – 100 years of radio in São Paulo: SQIG – Sociedade Rádio Educadora Paulista and PRA-6 Rádio Gazeta (Intercom - Brazilian Journal of Communication Sciences, 2023)
We discuss the history of radio, with a focus on SQIG Rádio Educadora Paulista and PRA-6 Rádio Gazeta. The question is about the circumstances and characteristics of the first radio station in São Paulo and the subsequent transfer of the call sign to Gazeta. The objective is to analyze and deepen our knowledge of the history of radio in the state, which celebrates its 100th anniversary in 2023. To achieve this, the methodology involves the analysis of primary memorial sources left by radio broadcaster Mauro Pires and interviews conducted with José Mauro Martins Pires, Mário Fannuchi, among others. The main references include Briggs and Burke, Moura and Nigri, Bosi, and Alberti. SQIG arrives in the city with great importance, boasting an excellent cast, and we conclude that it serves as a significant radio school, influencing generations of professionals and broadcasters.
Keywords: São Paulo radio; Sociedade Rádio Educadora; Paulista; Rádio Gazeta; Radio history; Radio and culture